A Rare Cause of Mechanical Icterus: Prostate Cancer Metastasis - Ozkahraman, Adnan; Durmaz, Ozan; Kayar, Yusuf (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Ozkahraman A, Durmaz O, Kayar Y. A rare cause of mechanical İcterus: prostate cancer metastasis. Turk J Gastroenterol. 2024;35(12):954-956.